A Study on the Influence of Cashew and Pawpaw Leaf on Soil Density Treatment of Contaminated Swampy and Clay Soils - Uku, Eruni Philip; Adianimovie Sakwe (International Journal of Advance in Molecular Engineering, 2025)
Soil density is a key parameter in assessing soil health and structure, often employed as a potential index in bioremediation studies. This study investigates the impact of bioremediation treatments using Cashew Leaf (Anacardium occidentale) and Pawpaw Leaf (Carica papaya) on the density of swampy and clay soils over time. The results show that both treatments, in varying quantities, influence the soil's density by reducing the post-contamination density to levels closer to the pre-contamination state. This research aims to contribute to understanding the relationship between soil density and bioremediation using organic amendments, with implications for improving soil structure and fertility. The behavior of Total Bacterial Count (TBC) and Total Petroleum Hydrocarbons (TPH) in clay soil mirrored that observed in swampy soil. During model evaluation, the correlation coefficient values (R²) derived from the Michaelis-Menten model were consistently higher than those from the first and second-order degradation rate models. Specifically, the R² values ranged from 0.9063 to 0.9894 for the first-order degradation rate, 0.8004 to 0.9396 for the second-order degradation rate, and 0.9639 to 0.9979 for the Michaelis-Menten equation. Therefore, the Michaelis-Menten equation provided a more accurate prediction of residual TPH compared to both the first and second-order degradation rate models.
Keywords: Cashew Leaf; Michaelis-Menten; Soil Density; Total Petroleum Hydrocarbons; bioremediation